ReTransformer: ReRAM-based Processing-in-Memory Architecture for Transformer Acceleration - Yang, Xiaoxuan; Yan, Bonan; Li, Hai; Chen, Yiran (Digest of technical papers - IEEE/ACM International Conference on Computer-Aided Design, 2020)
Transformer has emerged as a popular deep neural network (DNN) model for Neural Language Processing (NLP) applications and demonstrated excellent performance in neural machine translation, entity recognition, etc. However, its scaled dot-product attention mechanism in auto-regressive decoder brings a performance bottleneck during inference. Transformer is also computationally and memory intensive and demands for a hardware acceleration solution. Although researchers have successfully applied ReRAM-based Processing-in-Memory (PIM) to accelerate convolutional neural networks (CNNs) and recurrent neural networks (RNNs), the unique computation process of the scaled dot-product attention in Transformer makes it difficult to directly apply these designs. Besides, how to handle intermediate results in Matrix-matrix Multiplication (MatMul) and how to design a pipeline at a finer granularity of Transformer remain unsolved. In this work, we propose ReTransformer - a ReRAM-based PIM architecture for Transformer acceleration. ReTransformer can not only accelerate the scaled dot-product attention of Transformer using ReRAM-based PIM but also eliminate some data dependency by avoiding writing the intermediate results using the proposed matrix decomposition technique. Moreover, we propose a new sub-matrix pipeline design for multi-head self-attention. Experimental results show that compared to GPU and Pipelayer, ReTransformer improves computing efficiency by 23.21× and 3.25×, respectively. The corresponding overall power is reduced by 1086× and 2.82×, respectively.